2010
DOI: 10.1016/j.nbd.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cortex structure in prodromal Huntington disease

Abstract: Neuroimaging studies of subjects who are gene-expanded for Huntington Disease, but not yet diagnosed (termed prodromal HD), report that the cortex is “spared,” despite the decrement in striatal and cerebral white-matter volume. Measurement of whole-cortex volume can mask more subtle, but potentially clinically relevant regional changes in volume, thinning, or surface area. The current study addressed this limitation by evaluating cortical morphology of 523 prodromal HD subjects. Participants included 693 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
116
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 56 publications
17
116
4
Order By: Relevance
“…As our results show some changes (higher iron level) in the CST of Pre-HD subjects, but not significant motor cortex thickness reduction in Pre-HD, we suggest that WM damage may precede GM changes in the motor cortex. This hypothesis is in agreement with previous studies pointing in this direction in HD patients (Bartzokis et al 2007) and Pre-HD subjects (Nopoulos et al 2010). In any case, a future longitudinal investigation is needed to resolve this question.…”
Section: Discussionsupporting
confidence: 92%
“…As our results show some changes (higher iron level) in the CST of Pre-HD subjects, but not significant motor cortex thickness reduction in Pre-HD, we suggest that WM damage may precede GM changes in the motor cortex. This hypothesis is in agreement with previous studies pointing in this direction in HD patients (Bartzokis et al 2007) and Pre-HD subjects (Nopoulos et al 2010). In any case, a future longitudinal investigation is needed to resolve this question.…”
Section: Discussionsupporting
confidence: 92%
“…It is also possible that clinical characteristics, such as the estimated time to motor onset, could have contributed to negative findings. For instance, although in preHD less than 15 years from the estimated motor onset decreased striatal and cortical volume has been robustly detected using semiautomated analysis techniques [5,9,11,42,43], several studies have suggested that in preHD far from the estimated motor onset there may be no such structural changes when studied cross-sectionally [7,8,9] nor substantial rates of change over time [14,42]. We added to these reports in employing two additional techniques for structural analysis, cortical surface modeling and subcortical segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cross-sectional and longitudinal MRI studies have suggested that structural brain changes in carriers of the HD mutation may serve as biomarkers and potentially as surrogate endpoints in clinical trials [2,3,4,5,6]. However, intact brain structure in preHD has also been reported [7,8,9,10]. It is unlikely that these discrepancies can be solely explained by differing sample sizes, since clinical characteristics, such as the proximity to the onset of motor signs [5,11,12], and different analysis procedures [13] may also account for data heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations